Prosedur Pengeluaran Biaya Operasional Pada Badan Perencanaan Pembangunan Daerah Kabupaten Ende - Mariela Susana Leta; Zaenal Wafa (FKIP, Universitas Palangka Raya, 2023)
Agency activities always require funds to carry out its activities such as purchasing equipment, office needs and others. the expenditures of operating costs are used for office activities and purchase of Office equipment. how the procedure for the operation costs on the Development Planning Agency of the District of Ende there is a problem when it will be posted to the SPJ shopping at the time will be made often the treasury part wrong in entering the account number therefore SPJ data can not be processed and should be justified back so that there is no mistake then the part of the district should be more careful and careful in entering the number of the account. for the Procedure of Expenditure Costs is done well.